Partial Oxidation of Dimethyl Ether Using the Structured Catalyst Rh/Al2O3/Al Prepared Through the Anodic Oxidation of Aluminum - Yu, B. Y.; Lee, K. H.; Kim, K.; Byun, D. J.; Ha, H. P.; Byun, J. Y. (AMER SCIENTIFIC PUBLISHERS, 2011)
The partial oxidation of dimethyl ether (DME) was investigated using the structured catalyst Rh/Al2O3/Al. The porous Al2O3 layer was synthesized on the aluminum plate through anodic oxidation in an oxalic-acid solution. It was observed that about 20 nm nanopores were well developed in the Al2O3 layer. The thickness of Al2O3 layer can be adjusted by controlling the anodizing time and current density. After pore-widening and hot-water treatment, the Al2O3/Al plate was calcined at 500 degrees C for 3 h. The obtained gamma-Al2O3 had a specific surface area of 160 m(2)/g, making it fit to be used as a catalyst support. A microchannel reactor was designed and fabricated to evaluate the catalytic activity of Rh/Al2O3/Al in the partial oxidation of DME. The structured catalyst showed an 86% maximum hydrogen yield at 450 degrees C. On the other hand, the maximum syngas yield by a pack-bed-type catalyst could be attained by using a more than fivefold Rh amount compared to that used in the structured Rh/Al2O3/Al catalyst.
Keywords: HEXAGONAL PORE ARRAYS; ALTERNATIVE FUEL; DME